A bridge over troubled water? The Instrument contributing to Stability and Peace (IcSP) and the security-development nexus in EU external policy - Julian Bergmann (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
The enduring civil war in Syria, the fragile security situation in the Sahel and the armed conflict in Ukraine's Donbass region demonstrate that the European Union (EU) is currently confronted with complex security challenges. To provide an adequate response to these challenges, the EU seeks to implement a “joined-up” approach to its external action and strengthen its capacities at the interface of security and development policies. This paper analyses the European Union (EU)'s approach to the security-development nexus, focusing on the Instrument contributing to Stability and Peace (IcSP). The paper starts by placing the EU's approach to the security-development nexus in a broader context before demonstrating its manifestation in EU external policy discourse. Moreover, the paper discusses in what ways the EU has overcome its institutional fragmentation in managing the security-development interface. The paper then introduces the reader to the IcSP and presents empirical findings on the IcSP's impact. The analysis reveals that IcSP interventions make a valuable contribution to EU efforts in stabilising conflict and crisis situations and in preventing the escalation of violence. IcSP actions also contribute significantly to boosting partners' capacities for conflict prevention and peacebuilding both on a short-term and long-term basis. The IcSP makes a difference to EU external action as it provides the Union with a significant first-response capacity that has the potential to pave the way for longer-term EU engagement. However, there are challenges to swift decision-making and implementation as well as to coordination with other external financial instruments (EFIs). These challenges need to be overcome to maximise the IcSP's internal and external impact. Finally, the paper discusses how the debate about Capacity Building in Support of Security and Development (CBSD) has revealed deep-seated, diverging views on the relationship between EU security and development policy. The paper argues for filling the security-development nexus with further substance to avoid it becoming a mere buzzword that is used to instrumentalise development policy for security purposes. As the IcSP has proven its added value to EU efforts in conflict prevention and peacebuilding, it should be maintained during the next MFF period.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Sicherheit; Frieden und fragile Staaten